Pelatihan Pengasuhan untuk Meningkatkan Pemahaman dan Kualitas Pengasuhan Orang Tua Anak GPP/H - Setiyani, Ratna Yunita; Gamayanti, Indria Laksmi; Urbayatun, Siti (HUMANITAS, 2014)
ABSTRACTThis research was aimed to verify whether parenting training could improve the understanding about ADHD and quality care on parents of preschool children with ADHD. The research design was quasi experimental with non-randomized pretest-posttest control group design. The participants on this study were six people that were parents of preschool children with ADHD. This study tookplace in Jogja Citra preschool-kindergarten-day care, Pleret, Bantul. This research used Wilcoxon Mann Whitney and Kruskal Wallis as statistical analysis. The findings indicate that parenting training could improve parents understanding on ADHD and also improving the quality care of parents towards preschool children with ADHD. The data processing shows 0.039 < 0.05 for significance level of the understanding towards ADHD and 0.039 < 0.05 for quality care. The significance level of Kruskal Wallis hypothetical test is 0.020 < 0.05.Keywords: parenting training, understanding on ADHD, quality care